MORPHOFUNCTIONAL CHARACTERISTICS OF HEMOMICROCIRCULATORY BED’S VESSELS OF THE PANCREAS IN RATS AND AT CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS - Boruta, N.V. (World of Medicine and Biology, 2020)
In an experimental study of vessels of the hemomicrocirculatory bed of the exocrine pancreas in rats, it was found that the microvessels responded to the introduction of diferelin by persistent dilatation of arterioles during the first month of the experiment by 4.12% compared to the intact group of animals. The exchange component responded by increasing its average diameters, increasing its lumen by 1.93% compared to the intact animal group. The vessel capacity of the pancreas’ hemomicrocirculatory bed during the first month of the study responded with enlargement, increasing its lumens by 2.46% compared to the intact group of animals. The numbers recovery of the average diameters of microvessels with the introduction of tryptorelin embonate was not observed until the end of the experiment.
Keywords: vessels of the hemomicrocirculatory bed; pancreas; testosterone; rats